The Phillips Curve. A Classical Perspective - Muller Durán, Nancy; Perrotini Hernández, Ignacio (Papeles de Europa, 2020)
It is argued in this paper that a Classical Political Economy rendition of the original Phillips Curve (PC) (Phillips, 1958) provides a better understanding of the relationship between real wages and the rate of unemployment than the NAIRU hypothesis put forth by Friedman (1968, 1977). Hence a ‘Classical’ PC is here entertained to show the positive effect of increasing productivity on real wages. Our hypothesis is empirically tested using data for Germany, Spain, the United States and France. And the econometric results show the existence of high correlation between the variables emphasized by the Classical PC.
Keywords: Phillips Curve; Productivity; Real wage